Implementation of Virtual Reality as an Innovative Strategy in Tourism Marketing - Ida Ayu Adi Trisnawathi (Bali Tourism Board, 2025)
The tourism sector has undergone significant structural transformation in the post-COVID-19 era, driven by accelerated digitalization, changing tourist behavior, and heightened concerns regarding safety and accessibility. Within this context, Virtual Reality (VR) has emerged as an innovative technological strategy in tourism marketing, offering immersive and interactive experiences that go beyond conventional promotional media. This study aims to examine the role, implementation models, and strategic implications of VR in tourism marketing, with particular emphasis on its application in developing destination contexts such as Indonesia. Using a qualitative literature-based research design, this study address VR applications in tourism promotion, destination development, and visitor experience. Data were analysed thematically following the interactive model of Miles, Huberman, and Saldaña, focusing on three key dimensions: objectives of VR implementation, development frameworks employed, and impacts on tourist perception and behavior. The findings indicate that VR positively influences destination image, perceived attractiveness, and visit intention by enhancing cognitive and affective engagement while reducing perceived risk and psychological distance. Structured development models such as the Multimedia Development Life Cycle (MDLC) and ADDIE are found to support the creation of effective and user-friendly VR tourism applications. Furthermore, VR demonstrates potential to support sustainable tourism by promoting lesser-known destinations, redistributing tourism demand, and reducing physical pressure on environmentally sensitive sites.